2014
DOI: 10.3390/molecules19022261
|View full text |Cite
|
Sign up to set email alerts
|

On Tuning the Fluorescence Emission of Porphyrin Free Bases Bonded to the Pore Walls of Organo-Modified Silica

Abstract: A sol-gel methodology has been duly developed in order to perform a controlled covalent coupling of tetrapyrrole macrocycles (e.g., porphyrins, phthalocyanines, naphthalocyanines, chlorophyll, etc.) to the pores of metal oxide networks. The resulting absorption and emission spectra intensities in the UV-VIS-NIR range have been found to depend on the polarity existing inside the pores of the network; in turn, this polarization can be tuned through the attachment of organic substituents to the tetrapyrrrole ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
3
26
0
1
Order By: Relevance
“…This change might have been due to a change in the electronic structure in the porphyrin ring present in the chlorophyll molecules, because diols such as ethylene glycol can react with chlorophyll molecules to produce chlorophyllides . It has also been reported that the fluorescence intensity of the porphyrin ring‐containing molecules depends on the type of organic group attached to the porphyrin system …”
Section: Resultsmentioning
confidence: 99%
“…This change might have been due to a change in the electronic structure in the porphyrin ring present in the chlorophyll molecules, because diols such as ethylene glycol can react with chlorophyll molecules to produce chlorophyllides . It has also been reported that the fluorescence intensity of the porphyrin ring‐containing molecules depends on the type of organic group attached to the porphyrin system …”
Section: Resultsmentioning
confidence: 99%
“…The absence of traces of porphyrin complexes in the solvents employed to wash the ZrO 2 xerogel samples, together with the distinctive UV-vis signal pathways, demonstrate that, in both cases, the porphyrinic complex has been successfully bonded to the pore network in stable and monomeric respect to silica xerogels encapsulating CoT(p-COOH)PP species covalently bonded to the pore network, the average pore width was 3.1 nm [44,45]; i.e., a quantity that is very similar to the value determined for ZrO 2 xerogels. This similitude results obvious, if considering that the distance between the two opposite silicon atoms (d Si-Si ) in the CoP-F precursor, ranges from 3 to 3.25 nm (Fig.…”
Section: +mentioning
confidence: 95%
“…This rate is responsible of the creation of very small ZrO 2 precursory nucleating centers; whose formation insides on the textural parameters and pore morphology as follows; the large number of small particles creates compact aggregates, which are not giving access to their interior volume given the very small pore throats that connect them with neighboring pore cavities. Importantly, the porous structure can evolution from depicting a Type I to a Type IV isotherm by two alternative ways: (i) by increasing the annealing temperature of the xerogel [43] or (ii) by inserting relatively large macrocyclic molecules in the xerogel network as for instance dodecyltrietoxysilane [44]. The porous structure is opened up by the evolution of volatile materials still remaining in the xerogel structure(e.g.…”
Section: Nano Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds have diverse applications, including medicinal [ 1 ], electronic devices [ 2 ], energy conversion [ 3 ], catalysis [ 4 ], and others [ 5 , 6 , 7 ]. The range of applications for porphyrins can be attributed to some features observed in these molecules, including invariable planar shapes, effective absorption and emission, and high stability under different hazardous conditions [ 8 , 9 , 10 , 11 ]. Despite the numerous applications for porphyrins, their use in biomedical devices can be highlighted as one of their most prominent features.…”
Section: Introductionmentioning
confidence: 99%